The intelligent optimist's guide to life : how to find health and success in a world that's a better place than you think - Kamp, Jurriaan (Berrett-Koehler Publishers, 2014)
In this book, the author explains how we can cultivate an outlook of informed optimism by tuning out the media's focus on sensationalism and negativity and turning on our natural optimism.